Tax incentives to encourage corporate investment in Latvia - Hazans, Mihails; Pluta, Anna (University of Latvia, 2020)
During 2006‐2017, Latvia has applied a rather generous accelerated depreciation (AD) policy to stimulate firm investment. The AD policy included: (1) the general AD scheme, (2) incentives to acquire new technological equipment, and (3) Investment incentives in the specially assisted areas. This paper analyses the effect of accelerated depreciation policy on firm investment using administrative firm‐level data for 2007–14. Lacking data for a natural experiment (AD began before our sample period), we use difference‐in-differences methodology with identification based on variation either across time (the crisis period serving as quasi‐counterfactual) or by firm size (with large firms unlikely to be genuinely affected by the policy). We find that past use of AD had a positive effect on firm investment rates. The effect is stronger in industries with most of their assets in long-duration categories and among enterprises with fewer than six employees. AD of new equipment has a significant effect both on next year investment rate and on probability to invest next year, but only for firms with six to ten workers.
Keywords: tax incentives; corporate investment; accelerated depreciation; Research Subject Categories::SOCIAL SCIENCES::Business and economics